Plants present in the ancient malay garden according to old manuscripts and their effects on the formation of malay garden design model in Malaysia / Ahmad Zamil Zakaria , Ismail Hafiz Salleh and Mohd. Sabrizaa Abd Rashid - Zakaria, Ahmad Zamil; Salleh, Ismail Hafiz; Abd Rashid, Mohd. Sabrizaa (2012)
The purpose of this research was conducted is to find out the plants used by the Malay people in the ancient times either for medical purposes, food, landscaping and etc. The objectives of this research are to measure the image and culture of the Malays in Malaysia, which is applied in the design of the existing Malay Garden and also to identify the plants found in the existing Malay Garden. The method used in this research is, by referring to the old manuscripts and research papers done by researchers in the past about garden in the world of Malay Archipelago. The main manuscripts in this research are as Sulalatus al-Salatin (Malay Annals), Bustan al-Salatin (The Garden of Kings), Hikayat Hang Tuah, Hikayat Merong Mahawangsa, Hikayat Inderaputera, Hikayat Abdullah and also the book title Warisan Perubatan Melayu (Traditional Malay Medicine). Findings from this research can be concluded that the Malays in the past has had cultivation skills and also have knowledge about every function of plants have been planted by them. Knowledge possessed by the Malay people had inherited from generation to another generation. Therefore, to support a Malay garden design model, researchers have focused on the plant species that have been used either in the gardens in the past, especially the palace garden, the home of the Malays and the plants that grow in the vicinity of settlement of Malay at that time. Malay people are a special race, and there are many interesting elements through their creativity, such as songket weaving, carving, matting handicrafts, art in making handicrafts and architecture that may be highlighted, to become a model for the design of a Malay Garden.